Review of the Localization Law and its effect on the hiring of teachers - Ivy P. Mejia; Arlyne C. Marasigan; Jayson L. de Vera; Nikolee Marie A. Serafico-Reyes; Nilo J. Castulo; Cathlene de Pano; Leih Maruss V. Sinsay-Villanueva; Ivan Harris Tanyag; Jenard D. Berroya; Glenda Darlene V. Garcia; Valerie L. Lim; John Michael D. Aquino (Philippine Institute for Development Studies (PIDS), 2025)
The Localization Law (RA 8190) aims to improve educational equity by emphasizing the recruitment of teachers from local communities, promoting cultural congruence, and reducing relocation expenses. Although RA 8190 has been in effect since 1996, challenges on filling up teacher vacancies are still persistent. This study employed a descriptive qualitative research design, using document analysis, key informant interviews (KIIs), and focus group discussions (FGDs) with school administrators and teachers to assess the law's effectiveness and efficiency. Results highlighted that the law evolved over time to mandate a clear geographic hiring hierarchy while balancing local preference with subject specialization needs, particularly for priority programs supported by mechanisms like transfer priority and teacher ranking. Its implementation reveals significant limitations, such as teacher specialization mismatches, prolonged recruitment procedures, and a lack of effective and efficient monitoring and assessment mechanisms. The observed inconsistencies significantly affected teacher applicants and the school-level hiring and recruitment processes. This warrants further improvement in the implementation of the law to make it more effective and efficient. Therefore, it is essential to amend the law to ensure that the practice is monitored and evaluated in order to address the current challenges.
Keywords: 330; Localization Law; teacher recruitment; decentralization; educational equity; educational policy; educational practice